Stratigraphy und evolutionary patterns in middle jurassic ammonites ... - Mönnig, Eckhard (Deutsche Geologische Gesellschaft - Geologische Vereinigung e.V. (DGGV), 2023)
The biostratigraphy of the Jurassic system has made many advances in recent years. We can distinguish over 50 successive faunal horizons in the Callovian, which corresponds to a resolution of perhaps 75,000 to 100,000 years. The distribution of the ammonite genus Kepplerites in space and time has been extensively studied. This example illustrates the importance of a precise stratigraphy for paleontological and sequence-stratigraphic questions. The beginnings of the ammonite genus Kepplerites can be traced back to the Subboreal sea of NW Canada in the late Bathonian (Middle Jurassic). Thereafter the evolution can be followed over Greenland, the Russian platform over the Caucasus to Central Europe, up to its abrupt extinction at the beginning of the Callovian. Only a small population survived, probably in what is now the Caucasus. From here, a few specimens reached Central Europe and the Russian platform, where new species emerged (genetic drift). At the beginning of the Koenigi Zone, a species migrated from ...